P1077Late gadolinium enhancement with cardiac magnetic resonance imaging demonstrates left ventricular involvement is under-recognized in arrhythmogenic right ventricular cardiomyopathy. (18th June 2020) - Mohamed, S; Kunz, M; Casey, S; Katsiyiannis, W; Abdelhadi, R; Storey, K; Berg, A; Schmidt, C; Sengupta, J
Abstract: Funding Acknowledgements: The study is partially funded by Medtronic and the Minneapolis Heart Institute Foundation. Background/Introduction: Arrhythmogenic right ventricular cardiomyopathy (ARVC) is characterized by replacement of the myocardium with fibrous and fatty tissue that may lead to an increased risk of ventricular arrhythmias and heart failure. Although left ventricular (LV) and biventricular forms have been identified post-mortem resulting in the increased use of the term arrhythmogenic cardiomyopathy, there is only inclusion of right ventricular wall motion abnormalities in the taskforce diagnostic criteria. Purpose: The aim of our study was to examine the utility of cardiac magnetic resonance (CMR) imaging in characterizing LV or biventricular involvement with late gadolinium enhancement (LGE) in a large cohort of patients with suspected ARVC. Methods: Retrospective, single-institution, chart review of 76 patients diagnosed with ARVC between January 2009 and July 2019. Data collection and analysis included baseline demographics and parameters specific to diagnosis (definite, borderline, or possible) and risk stratification of ARVC based on 2019 modified taskforce criteria, as well as detailed CMR evaluation. Results: Of the 76 patients with ARVC, 66 (87%) had at least one CMR with gadolinium administered. In that subset of patients, 27 (41%) had LGE. Of those with LGE, LV involvement was identified in 23 (85%) patients. The pattern of LGE was not localized to one myocardial region but demonstrated variable LV enhancement patterns including anterior, inferior, lateral, septal, basal, mid, apical, and from the sub-epicardium into the mid-myocardium. Conclusions: Left ventricular involvement reflected by LGE was identified in a high percentage of patients with suspected ARVC, and there was significant variation in the pattern of distribution in terms of region and depth of myocardial involvement. While post-mortem examination of patients with ARVC demonstrates a high prevalence of left ventricular involvement, this study shows that CMR can consistently detect late gadolinium enhancement, and ARVC should be considered in the differential diagnosis for biventricular cardiomyopathy. The identification of variable locations of LGE within the LV suggests there is more than one phenotype, and this imaging modality may help to clarify the implications of left ventricular involvement in disease progression.